82.3k views
0 votes
HELP ASAP :(

How are the following three expressions different from each other, if indeed they are? do not just state the value of each but explain what may be the same or different. Be as specific as you can be in your response.
1.(-2)^2
2.-2^2
3. -(2)^2

User Otajor
by
4.8k points

1 Answer

5 votes

Answer:

1. 4

2. -4

3. -4

Explanation:

Let's look carefully at each problem and explain it.

1. (-2)^2

This means find the square of the number -2. Since the square of a number means multiplying the number by itself, then

(-2)^2 means the product (-2) * (-2),

and since the product of two negative numbers is positive, then

(-2)^2 = (-2) * (-2) = 4

Answer is 4.

2. -2^2

Here, the exponent applies only to the 2, not to -2. This problem means square 2 and then take the opposite of the product. This can be written as

-(2^2)

-2^2 = -(2^2) = -(2 * 2) = -(4) = -4

Answer is -4.

3. -(2)^2

This is the same as problem 2 above. You square the 2 first, then take its negative.

-(2)^2 = -(2^2) = -(2 * 2) = -(4) = -4

Answer is -4

User Thirupparan
by
5.5k points